The influence of leadership styles on employee commitment in the retail industry - Mqomboti, Sakhile (Rhodes University, Faculty of Commerce, Rhodes Business School, 2019)
Purpose "“ Companies operating in the South African retail industry have been experiencing a high staff turnover, reported to be standing at 36% (Kelly, 2016). The Edcon Retail Group and Taste Holdings have already indicated their strategic focus on staff turnover reduction in order to achieve their business objectives (Crotty, 2017; Laing, 2017). This research study explained the relationship between the three leadership styles of the Full Range Leadership Theory (FRLT) model developed by Bass and Avolio and three types of commitments from the three component model of Meyer and Allen. The research study was interested in the leadership style that contributes the most to commitment. The effective leadership style may be developed to improve the level of employee commitment in the South African Retail industry. Methodology "“ The research study used the total population of 300 subordinate employees from four stores of a retail company in the Rustenburg region in the North-West Province of South Africa. The Multifactor Leadership Questionnaire (MLQ 5X) instrument was adopted for leadership questionnaire data collection, the three-component model of commitment was adopted for data collection of the commitment questionnaire. Pearson Correlations quantitative data analysis was adopted to explain the relationship of the independent and dependent variables. Multiple Regression quantitative data analysis was adopted to test the strength of the leadership styles on commitment. Findings "“ The statistical analysis results of Pearson Correlations found weak but significant positive relationship between Transactional leadership style and both Normative and Continuance commitment. A weak but significant positive relationship was found between Transformational leadership style and Normative commitment. A weak but significant positive relationship was found between Passive/Avoidant leadership and continuance commitment. Transformational leadership style showed more strength in contribution to commitment, followed by the Transactional leadership style. Significant "“ This research study will expand the existing but limited leadership style and commitment body of knowledge in the South African retail industry. The South African retail companies will be able to develop the preferred leadership style by its employees and develop this leadership style in their managers to improve the commitment of their employees.
Keywords: Retail trade -- Management -- South Africa; Retail trade -- Employees -- South Africa; Employee loyalty -- South Africa; Leadership -- Case studies -- South Africa